The Analysis of Personal Handicap Manifestations of Personality Using Projective Technique «I met a disabled person» - Nazarevich, Victoria Vyacheslavovna (Psychological Prospects Journal, 2012)
In the article author reveals the features of the introduction and analysis of main tendencies using of projective technique «I met a disabled person» that can define personality traits of handicap manifestations.
Keywords: handicapism drawing projective technique